Réponses

Meilleure réponse !
2014-10-19T21:21:49+02:00
A = 1/5 x - 4/3 + 7/2
A = - 4/15 + 7/2
A = - 4 x 2 / 15 x 2 + 7 x 15 / 2 x 15
A = - 8/30 + 105/30
A = 75/30
A = 15 x 5 / 15 x 2
A = 5/2

B = 4/5 : (- 3/7) - 7/10
B = 4/5 x - 7/3 - 7/10
B = - 28/15 - 7/10
B = - 28 x 10 / 15 x 10 - 7 x 15 / 10 x 15
B = - 280/150 - 105/150
B = 385/105
B = 35 x 11 / 35 x 3
B = 11/3

C = 13/7 + (- 8/7) : (-4/5)
C = 13/7 + (-8/7) x (- 5/4)
C = 13/7 + 40/28
C = 13 x 4 / 7 x 4 + 40/28
C = 52/28 + 40/28
C = 92/28
C = 4 x 23 / 4 x 7
C = 23/7

D = 7/3 + 3/2 x - 10/21
D = 7/3 - 30/42
D = 7 x 14 / 3 x 14 - 30/42
D = 98/42 - 30/42
D = 68/42
D = 2 x 34 / 2 x 21
D = 34/21

E = 5/8 + (- 3/4) : (- 9/16)
E = 5/8 + (- 3/4) x (- 16/9)
E = 5/8 + 48/36
E = 5 x 36 / 8 x 36 + 48 x 8 / 36 x 8
E = 180/288 + 384/288
E = 564/288
E = 12 x 47 / 12 x 24
E = 47/24

F = 6/5 - (- 1/9) x (- 3/4)
F = 6/5 - (3/36)
F = 6 x 36 / 5 x 36 - 3 x 5 / 36 x 5
F = 216/180 - 15/180
F = 201/180
F = 3 x 67 / 3 x 60
F = 67/60


a) 3x² + 5x - 3 = 6x + 1
Pour x = 4/3

3 * 4²/3² + 5 * 4/3 - 3 = 6 * 4/3 + 1
3 x 16/9 + 20/3 - 3 = 24/3 + 1
48/9 + 20/3 - 3 = 24/3 + 1
48/9 + 20 x 2 / 3 x 3 = 24 x 3 / 3 x 3 + 1 x 9 / 1 x 9
48/9 - 40/9 = 72/9 + 9/9
8/9 ≠ 81/9
L'égalité est fausse

b) x - 1 = - 3x + 2
   2x + 5       x - 3
Pour x = - 1/4

- 1/4 - 1        = - 3 * - 1/4 + 2
2 * -1/4 + 5      - 1/4 - 3
- 1/4 - 1 x 4 / 1 x 4 = 3/4 + 2 x 4 / 1 x 4
- 2/4 + 5 x 4 / 1 x 4  - 1/4 - 3 x 4 / 1 x 4
= - 1/4 - 4/4    = 3/4 + 8/4
   - 2/4 + 20/4    - 1/4 - 12/4
= - 3/4 11/4
     18/4   11/4
L'égalité est fausse